EMT-like circulating tumor cells in ovarian cancer patients are enriched by platinum-based chemotherapy - Chebouti, Issam; Kasimir-Bauer, Sabine; Buderath, Paul; Wimberger, Pauline; Hauch, Siegfried; Kimmig, Rainer; Kuhlmann, Jan Dominik (OncoTarget, 2017)
https://doi.org/10.18632/oncotarget.16179 Issam Chebouti, Sabine Kasimir-Bauer, Paul Buderath, Pauline Wimberger, Siegfried Hauch, Rainer Kimmig, Jan Dominik Kuhlmann